UPAYA PENINGKATAN KINERJA PERAWAT GAWAT DARURAT MELALUI BERBAGAI GAYA KEPEMIMPINAN DI RSUD DAERAH ISTIMEWA YOGYAKARTA - Rahadian Syah, Deby Zulkarnain; Nofiyanto, Muhamat (Media Ilmu Kesehatan, 2017)
Background: Nurses in charge of the Emergency Room are required to have more ability than nurses serving patients in other units. Emergency Room is an initial service in a hospital. One's leadership style will greatly affect the effectiveness of a leader. The selection of the right leadership style can lead to the achievement of individual or organizational goals. Objective: To know the various leadership style used by the head of room in improving the performance of nurses of Emergency Room RSUD in in Special Region of Yogyakarta. Method: This research includes quantitative research type, using cross sectional approach. The population of this study was the head of the treatment room. Secondary data of nurse's performance is taken from nursing care which is written in medical record file of Emergency Room of RSUD in Special Region of Yogyakarta. Results: The performance of nurses at Emergency Room RSUD A in the good category was 100%. The performance of nurses at Emergency Room RSUD B in the enough category was 45%. The performance of nurses at Emergency Room C in good category was 80%. The performance of nurses at Emergency Room RSUD D in good category was 55%. The performance of nurses at RSUD E in the good category was 95%. The result of cross tabulation between leadership style and nurse performance of RSUD in the whole DIY with good performance is leader who use democratic leadership style equal to 35%. Conclusion: Most of the nurse's good performance in Emergency Room is followed by democratic leadership style of head of space.  Keyword: leadership style, head of space, performance of nurses